Reisebilder : Berichte zur zeitgenössischen Kunst - Gachnang, Johannes; Andersen, Troels (Wien : Sonderzahl Verlagsgesellschaft m.b.H., 1985)
Chaissac, Gaston ; Klossowski, Pierre ; Oppenheim, Meret ; Penck, A.R. ; Baselitz, Georg ; Kiefer, Anselm ; Immendorff, Jörg ; Lüpertz, Markus ; Nitsch, Hermann ; Brus, Günter ; Rainer, Arnulf ; Vedova, Emilio ; Kirkeby, Per ; Zaugg, Remy
Duits
boek